Comunicación oral en el pueblo de guangaje: lengua kichwa frente al idioma español. - Manzano Manzano, Darwin Geovanny (2018)
The present investigation intends to identify the characteristics with which the psychodynamics of oral culture are manifested in the indigenous population of Guangaje. The main objective is to examine the differences of these psychodynamics between Kichwa speakers, bilinguals and Spanish speakers of the aforementioned parish, located in Pujilí canton, Cotopaxi province. In order to achieve this objective, a bibliographical research was carried out to support the theoretical and conceptual analysis of the forms of oral expression. Regarding the methodology, the qualitative approach was implemented, using the focus group technique and the unstructured interview, both of which allowed identifying relevant aspects of identity, the transcendence of ancestral knowledge and cultural exchange, which define the ways of being and to act of the inhabitants in this parish. Among the results obtained from the focus group and the unstructured interview, there is a multiple psychodynamic approach in the indigenous town of Guangaje, where oral culture facilitates the transmission of the wisdom of nature, religion, Andean culture and the ancestral language , which historically have been represented with stories, legends and stories.Older adults, likewise, conserve the oral culture of the people and have chosen to maintain their ancestral language and knowledge without changes, while young adults only do so partially, due to the influence of Spanish and writing (reading and technology). The young Kichwas of Guangaje have adapted more to Spanish, to access spaces where miscegenation dominates, trying not to renounce their own identity elements. Keywords: Oral culture, bilingualism, Spanish speakers, indigenous population, Kichwa language.